Characterization of ERV-6 env as a Potential Biomarker and Driver of Migration in Multiple Cancer Lineages - Alshamarti, Ibtihal (Asian Pacific Journal of Cancer Biology, 2026)
Background: Metastasis is the primary cause of cancer mortality, and genomic elements such as endogenous retroviruses (ERVs) are increasingly recognized as potential drivers of this process. This study investigates the characterization of ERV-6 env as a biomarker and a regulator of migration across multiple cancer lineages. the ERV family (specifically ERV-6) remains in the human genome sequence and may still be biologically active, recent bioinformatics analyses in genome sequencing have investigated crucial roles of ERV-6 env in caner disease, for example breast, colon, pancreatic, and skin cancer. Thus, the map of ERV -6 sequencing is a key to explaining the role of disease and cancer related to ERV-6 activation. Methods: To detected the ERV-6 in different cancer cell lines (T24 –Bladder, MCF7-Breast, CDKN2A-pancreatic, H460-Lung, SKOV3- Ovarian, and B16F10-Melanoma). PCR and nested PCR were done and measure the metastatic rate by using migration assay to showed role ERV-6 env to induce migration cancer cell lines. Results: Our data investigate that ERV-6 env was showed in all breast, bladder, pancreatic, lung, ovarian and melanoma cancer cell lines. In addition, specific amplicons showed in cell line, potentially reflecting novel ERV-6 env insertions. Although, ERV-6 was increased level of migration in different points time, the B16F10 cell recorded a significantly aggressive migratory level. The gap is nearly completely filled by cells at the 48-hour mark, in contrast to other cancer cell lines. Conclusion: Therefore, an ERV-6 env significantly impacts the ability of cancer cells to migrate (metastatic) and ERV-6 env plays a critical role as a valuable diagnostic biomarker.